Gestión de control de inventarios y su impacto en los estados financieros de la Empresa Disprotextil S.A. periodo 2018 – 2019 - Velásquez Vargas, Yessenia Dayanara (2020)
Through the completion of this research project, the situation and management of the inventories and their impact on the financial statements in the company DISPROTEXTIL SA were analyzed during the 2018-2019 period, a company dedicated to the marketing and distribution of footwear at the level National, through catalogs. The investigation was in the area of inventories, in the lack of an inventory management system, which allows agility and promptness in the processes immersed in the stock, as well as deficiencies that affected the financial statements, the lack of process and function manuals, which is why employees were stuck in everyday processes and activities. A broad bibliographic source was used to support this research, based on theories and reports relevant to it. Through the interview and survey, accurate information was collected to demonstrate the lack of an inventory management system in the area of stocks. The calculation of the main financial ratios, such as the performance and efficiency index, through its gross profit margin and sales growth rates, the profitability of sales and the turnover rate, served as support and corroboration of the main objectives of this investigation.